Basel III and SME bank finance in Germany - Philipp Marek; Ingrid Stein (Deutsche Bundesbank, 2022)
This paper examines how Basel III capital reforms affected bank lending in Ger- many. We focus on the increase of minimum risk-based capital requirements and the introduction of the leverage ratio. The announcement of stricter risk-based capital regulation significantly affected low capitalized banks. The impact depends on a bank's credit risk model, i.e. whether a bank applies the standardized approach (SA) or an internal ratings-based approach (IRBA) to determine risk weights. Low capitalized SA banks significantly cut lending whereas IRBA banks did not ad- just lending volumes. By contrast, low capitalized IRBA banks significantly in- creased collateralization while low capitalized SA banks adjusted collateralization only marginally. Moreover, the impact on SMEs and large companies also differs. In terms of lending, SMEs were affected more strongly, whilst in terms of collateralization the impact on large companies was bigger. The announcement of the leverage ratio had, however, a rather limited impact. We find some evidence that low capitalized banks reduced lending. Furthermore, low capitalized banks somewhat tightened collateral requirements, especially for large companies.
Keywords: D22; E58; G21; 330; Basel III; bank lending; nancial regulation; small and medium-sizedenterprises (SMEs)